2019
DOI: 10.1021/acs.macromol.8b02416
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Heterogeneity in the Curing Process of an Epoxy–Amine System

Abstract: Epoxy resins are composed of a three-dimensional network formed by chemical reactions between epoxy and amino compounds, which plays an important role in the mechanical properties. Thus, to use epoxy resins in various applications, it is necessary to gain a better understanding of their network structure. Here, we study the structural heterogeneity evolved in an epoxy−amine mixture during the curing process on the basis of a particle tracking technique, in which the thermal motion of probe particles in the mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 53 publications
5
80
0
Order By: Relevance
“…The SANS data are consistent with models developed for cross-linked polymer gels [35][36][37][38] and later applied to thermosets [39][40][41][42]. Thus, the total scattering is given by the sum of two separate contributions: I(Q) tot = I(Q) L + I(Q) S due to small structures at high Q, I(Q) L , and large structures, I(Q) S , at low Q.…”
Section: Structural Changes During Curing and Phase Separationsupporting
confidence: 80%
“…The SANS data are consistent with models developed for cross-linked polymer gels [35][36][37][38] and later applied to thermosets [39][40][41][42]. Thus, the total scattering is given by the sum of two separate contributions: I(Q) tot = I(Q) L + I(Q) S due to small structures at high Q, I(Q) L , and large structures, I(Q) S , at low Q.…”
Section: Structural Changes During Curing and Phase Separationsupporting
confidence: 80%
“…Future studies are needed to investigate the dynamics of these various epoxy resins to provide a more general insight. Moreover, although we used the nanoparticles having diameters of 120 nm in the present study, it has been reported in particle-tracking measurements of the curing process of an epoxy-amine mixture that the particle size can affect particle movement 53 . Thus, it will be interesting to analyze the size dependence of probe particles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ∆E a value depends on the combination of epoxy and amine, the current objective is to gain insight to the effect of molecular size. Hence, the values obtained experimentally in the previous studies were here used [28][29][30] . That is, the values for the 1 st and 2 nd reactions were 56.8 and 55.3 kJ‧mol −1 , respectively.…”
Section: Simulationsmentioning
confidence: 99%
“…The heat generated by the reaction was taken into consideration by raising the kinetic energy of molecules involved in the reaction. The value of heat of formation, 58.6 kJ‧mol −1 , which was obtained in previous experiments was set for the both reactions [28][29][30] .…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation